Insights into economic charter change and the case for services reform - Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2024)
This essay discusses the rationale for economic charter change through the lens of services reform and identifies three issues with the current proposal of Congress: the retention of the legislative franchise requirement, the exclusion of mass media from the scope of the amendments, and the choice of the liberalization approach. To harness the full potential of services as an engine of economic growth and development in the 21st century, the paper recommends addressing these issues and removing all the specific restrictions that have been locked in the 1987 Constitution, namely: Art. XII Sec. 11 (public utility), Art. XII Sec. 14 (practice of all professions), Art. XIV Sec. 4(2) (educational institutions); Art. XVI Sec. 11(1) (mass media); and Art. XVI Sec. 11(2) (advertising industry). Liberalization must be pursued as part of a broader structural reform agenda. This involves improving regulations and strengthening institutions that will foster an economic environment that supports robust competition, encourages innovation, and facilitates the efficient allocation of resources. The reforms will contribute to higher productivity, which the Constitution itself recognizes "as the key to raising the quality of life for all, especially the underprivileged" (Art. XII Sec.1).
Keywords: 330; services; restrictions; trade; investment; regulation